In vitro androgenic response of sunflower - (:unkn) unknown (Nova Science Publishers, Inc., 2020)
Sunflower (Helianthus annus L.) is one of the most important oil seed crops cultivated worldwide. Despite increasing need for sunflower cultivation, the plantation area has decreased depending on seasonal variations in temperature with negative impact on yield. An isolated microspore and anther culture provides an excellent system for the study of microspore induction and embryogenesis, and can produce doubled haploid plants, which are useing to accelerate plant-breeding programs. The in vitro androgenic response of sunflower was investigate using Nitsch (NLN) for microspore culture and Murashige and Skoog (MS) culture media for anther culture to ascertain the effectiveness of androgenesis in this study. Different pretreatments (24 hours, 48 hours, 72 hours +4-C cold and 2, 4, 8, 12 days +35-C hot pretreatments), types of auxin (NAA, IAA, 2.4D), and different genotypes (IMI-K0-R-SN-7/13, IMI-K3-R-SN-8/13, SURES-K5-R-SN-4/13, SURES-K0-A-SN-1/13) are researched to get androgenic sunflower by using anther cultur method. Number of the anthers, calli and embryogenic calli, number, structure and percentage of regeneration, percentages of calli and embryogenic calli parameters were considered and the most effective pretreatment, auxin type and genotype were described as 12 days +35-C hot treatment, NAA plant growth regulator and SURES-K5-R-SN-4/13 genotype, respectively. Also, obtaining callus was achieved from isolated microspors in NLN suspension cultures incubated at 25°C. The present study has been an attempt to develop a suitable protocol for androgenic response of sunflower have yielded useful information for both understanding androgenesis and improving the efficiency of doubled haploid production. © 2020 Nova Science Publishers, Inc. All rights reserved.
Keywords: Anther culture; Microspore culture; Sunflower